APLIKASI FUNGSI MANAJEMEN PENGELOLA LAYANAN KOMPREHENSIF BERKESINAMBUNGAN HIV-IMS PUSKESMAS DI KOTA SEMARANG TAHUN 2014 - Utami, Intan Rahayu; Sriatmi, Ayun; Wigati, Putri Asmita (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Humman Immunodeficiency Virus (HIV) in the city of semarang experienced an increase from 427 cases in 2011 be 520 cases in 2012 and 430 cases in 2013. This research aims to analyze the application of Comprehensive Ongoing Service management function of HIV-IMS in health center. This research is descriptive research that uses qualitative approach. The collection of data using interview method to 4 main informant and 5 triangulation informant. The results of this research showed that the planning function has been going including identification of problems, analyze risk of factors and the preparation of action plan, The function of organizing for the establishment of the implementing team have been done during the training activities but there are still some positions/expertise that does not exist, for the formulation of job networking activities are already well corresponding with the duties and function. The implementation function of training activities has already been given, but there is still some training that has not been given in accordance with that stated in the manual implementation of LKB-HIV-STI. Supervisory function consists of internal supervision and external supervision from the Distric Health Office. Conclusion from this research the aplication of management fuction have been done in this service management and suggestion for the Distric Health Office is to do the supervision regularly.